CLUBE DESPORTIVO NUN'ÁLVARES: Por uma Gestão Desportiva Moderna do clube e do seu Parque Desportivo - Tiago Nuno de Jesus Flores Vasquez (2018)
This essay describes the work experience attained as part of the Master in Sports Management, attended in the Faculty of Sports in the University of Porto. The internship took place in the Club Sportivo Nun'Álvares, from November 2017 until July 2018. The main purpose of this internship is to be in a position to learn and describe the regular working of the Club Sportivo Nun'Álvares, preparing a critical review, and also looking at the voluntary sports club and the social movement behind it, comparing it with the modern management model of sports associations. This experience resulted factually in the development of knowledge and understanding and acknowledging the rich relationships that are developed in a voluntary sports club. Focus was on the club management, looking at the decision making process while attending the weekly/fortnight management meetings, where you can see what does the club need to actually work. This essay is divided in 5 chapters, following a normal model, explaining the internship initially, describing the sports club, and then engaging the framework of the professional training, the realization of professional practice and the final conclusion and reflexion. This conclusion makes an effort in showing the complex relationships arising in the club, giving ideas that can be used to modernize the club's management, bringing it forward.